2019
DOI: 10.4103/shb.shb_39_19
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of spiritual coping strategies on caregiving burden and mental health in caregivers of Iranian patients with dementia

Abstract: Introduction: Dementia is a common cognitive disorder among elderly people requiring special care. Family carers of people with dementia (PWD) may experience mental health issues. This study examined whether spiritual coping is a mediator between the physical function of the patients and mental health status or caregiving burden in their carers. Methods: The caregivers of the PWD (n = 513) were assessed by the Instrumental Activities of Daily Living (IADL) and Spiritual Coping Strategies (SCS) questionnaires a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(30 reference statements)
2
1
0
Order By: Relevance
“…However, in the face of these challenges, positive religious coping emerges as a critical resource, as evidenced by the significant mediating effects it exhibits on the relationship between caregiver burden and mental health outcomes. This finding is consistent with the literature on caregiving in other contexts, such as dementia, where spiritual coping strategies significantly buffered the mental health impacts of caregiving (30,31). The preference for positive religious coping over negative coping mechanisms among caregivers of thalassemia patients further underscores the adaptive role of faith-based strategies in managing caregiver stress (8).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, in the face of these challenges, positive religious coping emerges as a critical resource, as evidenced by the significant mediating effects it exhibits on the relationship between caregiver burden and mental health outcomes. This finding is consistent with the literature on caregiving in other contexts, such as dementia, where spiritual coping strategies significantly buffered the mental health impacts of caregiving (30,31). The preference for positive religious coping over negative coping mechanisms among caregivers of thalassemia patients further underscores the adaptive role of faith-based strategies in managing caregiver stress (8).…”
Section: Discussionsupporting
confidence: 87%
“…This dual role of caregiver burden highlights the complex dynamics caregivers navigate, balancing stress and coping mechanisms to maintain their mental health. Notably, the study also identified that positive religious coping significantly enhances psychological well-being and mitigates psychological distress (22,30), aligning with the hypothesis that positive religious coping acts as a mediating factor between caregiver burden and mental health outcomes. Previous studies, such as those by Anum & Dasti (22) and Chen et al (24), have similarly reported a negative correlation between caregiver burden and both mental and physical health, thereby reinforcing the general consensus that higher caregiver burdens are detrimental to health.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation